Teachers’ Perspectives on Using Interactive Digital Storytelling for EFL Instruction in Rural Indonesia - Pujiani, Tri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Although digital storytelling is greatly promoted for language acquisition, little is known about teachers' perceptions towards its practical application, especially in rural EFL settings. This qualitative study examines how EFL teachers teaching in rural kindergarten of Banyumas Regency perceive the use of interactive digital storytelling to assist young learners' acquisition of language. Through semi-structured interviews, this research identifies perceived benefits in the form of enhanced interaction, recall of vocabulary, and contextual knowledge, and salient obstacles in the form of limited infrastructure, digital competence, and insufficiencies in mapping content to national curriculum levels. The study underscores teacher professional development and localized content alignment needs. This study contributes to the discourse on equitable language learning resources and supports SDG Goal 4 through proposing education innovation that is attentive to education disparities.